Celiac disease and the risk of kidney diseases: A systematic review and meta-analysis - Karn Wijarnpreecha (2018)
© 2016 Editrice Gastroenterologica Italiana S.r.l. Background/objectives Previous epidemiologic studies attempting to demonstrate the risk of kidney diseases among patients with celiac disease (CD) have yielded inconsistent results. This meta-analysis was conducted with the aims to summarize all available evidence. Methods A literature search was performed using MEDLINE and EMBASE from inception to May 2016. Studies that provided relative risks, odd ratios, or hazard ratios examining the risk of kidney diseases among patients with CD versus individuals without CD were included. Pooled risk ratios (RR) and 95% confidence interval (CI) were calculated using a random-effect, generic inverse variance method. Results Eight studies met our eligibility criteria and were included in our analysis. A pooled RR of overall kidney diseases in patients with CD was 2.01 (95% CI, 1.44–2.81, I2 = 76%). The pooled RR of end-stage renal disease in patients with CD was 2.57 (95% CI, 2.03–3.24). Subgroup analyses showed that significant risks were increased for diabetic nephropathy (pooled RR of 1.49, 95% CI, 1.09–2.02) and IgA nephropathy (pooled RR of 2.62, 95% CI, 1.27–5.42) in patients with CD. Conclusions Our study demonstrates a significantly increased risk of kidney diseases among patients with CD. These findings may influence clinical management and primary prevention of kidney diseases in patients with CD.